Climate and Health in Buenos Aires: A Review on Climate Impact on Human Health Studies Between 1995 and 2015 - Fontan, Silvia; Rusticucci, Matilde (Frontiers in Environmental Science, 2021)
Abstract: In this review, seven researches about climate variability and its impact on human health in Buenos Aires City between 1995 and 2015 were evaluated. It´s been highlighted continuities and ruptures in the methodology, variables, and statistics data, considering their coincidences and differences in the period of study and the methodology applied. Contributions and pending issues were considered in order to improve living conditions and public policies facing climate change challenges in this city. Six studies Contributed to endorse evidence on the relationship between climate and health and its impacts on population, two of them were considered to develop early warning systems and one study is a preliminary approach.